Improvement of psychological work in the system of moral and psychological support for the operational activities in the internal affairs personnel - Vladimir L. Kubyshko (Национальный психологический журнал, 2017)
Background. Since psychological work in the Ministry of Internal Affairs of the Russian Federation is one of the professional activities, the departments must perform the tasks of the following two tiers: professionally-based and system-wide. Those tasks of the first tier perform the tree groups of individual and group diagnostics, personal and professional development, and professional and psychological support. When implemented they are determined by system-wide goals, with the main one shaping the patriotic worldview, corporate culture and the significantprofessionalproperties of the employees. Objective. Within the framework of the approach mentioned above, the paper considers static and dynamic models of psychological work in the Ministry of Internal Affairs of the Russian Federation at the present stage, current issues and ways to resolve them are revealed. Progress Report. Based on the brief analysis of the static model of psychological work it is concluded that there are forces and means for the successful accomplishment of the assigned tasks which is confirmed by the external indicators. When considering the on-line dynamic model issues, the issues of scientific and methodological character are identifiedand also the corporate personnel and the systemwide (worldview) typeof work are determined. Their essence and content are specified, and also the ways to constructively eliminate these issues are highlighted. Research results. The author emphasizes that the worldviewissues require special consideration as their solution demand a set of measures connected with the extension of the functional duties of the psychologists working in the Ministry of Internal Affairs. Conclusion. In the conditions of negative information and psychological impact on the professional and corporate consciousness of the Ministry of Internal Affairs employees, the increased attention of some researchers to the negative moments of the history of the police when its heroic pagesare ignored, the psychologists should use the entiretoolkit of psychological approaches and methods to withstand the aforementioned destructive influences. Particular importance should be attached to the development of the employeemotivational sphere as the most important component of their career orientation.